PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR (Studi Pada Konsumen Pengguna Sepeda Motor Yamaha Mio di Pemalang) - Nisrinna Dwi Sagarawanti; Wahyu Hidayat (Universitas Diponegoro, 2018)
se decision of Yamaha Mio motorcycle in Pemalang District. The population of this study is all consumers who purchase Yamaha Mio motorcycles in Pemalang District in 2016. The sample used is 100 respondents, while the sampling technique using cluster sampling method (sample area). Data analysis technique used is multiple linear regression analysis. The research used questionnaire method, that is by giving questionnaire containing question to the respondent of the research to give answer to the statement, then processed by using SPSS 17.0 to get valid research result. The result of equation obtained from multiple linear regression analysis shows that product quality and price variable have positive effect to purchasing decision. Hypothesis test results show that 1). Variable of product quality have positive and significant effect to purchasing decision, 1). Price variables have a positive and significant effect on purchasing decisions. The results of simultaneous test showing that product quality and price together have a significant effect on purchasing decision.